Control of acute myeloid leukemia and generation of immune memory in vivo using AMV564, a bivalent bispecific CD33 x CD3 T cell engager. - Linda G Eissenberg; Julie K Ritchey; Michael P Rettig; Dilan A Patel; Kiran Vij; Feng Gao; Victoria Smith; Tae H Han; John F DiPersio (PLoS ONE, 2024)
Off-the-shelf immunotherapeutics that suppress tumor growth and provide durable protection against relapse could enhance cancer treatment. We report preclinical studies on a CD33 x CD3 bivalent bispecific diabody, AMV564, that not only suppresses tumor growth, but also facilitates memory responses in a mouse model of acute myelogenous leukemia (AML). Mechanistically, a single 5-day treatment with AMV564 seems to reduce tumor burden by redirection of T cells, providing a time window for allogeneic or other T cells that innately recognize tumor antigens to become activated and proliferate. When the concentration of bispecific becomes negligible, the effector: target ratio has also shifted, and these activated T cells mediate long-term tumor control. To test the efficacy of AMV564 in vivo, we generated a CD33+ MOLM13CG bioluminescent human cell line and optimized conditions needed to control these cells for 62 days in vivo in NSG mice. Of note, not only did MOLM13CG become undetectable by bioluminescence imaging in response to infusion of human T cells plus AMV564, but also NSG mice that had cleared the tumor also resisted rechallenge with MOLM13CG in spite of no additional AMV564 treatment. In these mice, we identified effector and effector memory human CD4+ and CD8+ T cells in the peripheral blood immediately prior to rechallenge that expanded significantly during the subsequent 18 days. In addition to the anti-tumor effects of AMV564 on the clearance of MOLM13CG cells in vivo, similar effects were seen when primary CD33+ human AML cells were engrafted in NSG mice even when the human T cells made up only 2% of the peripheral blood cells and AML cells made up 98%. These studies suggest that AMV564 is a novel and effective bispecific diabody for the targeting of CD33+ AML that may provide long-term survival advantages in the clinic.